Spectropolarimetric observations of an arch filament system with the GREGOR solar telescope. Issue 10 (29th November 2016) - Balthasar, H.; Gömöry, P.; González Manrique, Sj.; Kuckein, C.; Kavka, J.; Kučera, A.; Schwartz, P.; Vašková, R.; Berkefeld, T.; Collados Vera, M.; Denker, C.; Feller, A.; et al.
Abstract: Arch filament systems occur in active sunspot groups, where a fibril structure connects areas of opposite magnetic polarity, in contrast to active region filaments that follow the polarity inversion line. We used the GREGOR Infrared Spectrograph (GRIS) to obtain the full Stokes vector in the spectral lines SiI λ 1082.7 nm, HeI λ 1083.0 nm, and CaI λ 1083.9 nm. We focus on the near‐infrared calcium line to investigate the photospheric magnetic field and velocities, and use the line core intensities and velocities of the helium line to study the chromospheric plasma. The individual fibrils of the arch filament system connect the sunspot with patches of magnetic polarity opposite to that of the spot. These patches do not necessarily coincide with pores, where the magnetic field is strongest. Instead, areas are preferred not far from the polarity inversion line. These areas exhibit photospheric downflows of moderate velocity, but significantly higher downflows of up to 30 km s –1 in the chromospheric helium line. Our findings can be explained with new emerging flux where the matter flows downward along the field lines of rising flux tubes, in agreement with earlier results. (© 2016 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)